‘Log’ KyaKahenGey?! (What will ‘people’ say?!): Complicating Sexuality and Empowerment with Community Development Workers in Pakistan - Shama Dossa (Adult Education Research Conference, 2011)
Situated in the postcolonial modernizing discourse of development, empowerment narratives tend to present sexuality as a secondary issue and a private affair one in which ‘development should keep an appropriate distance’ with the exception of helping to reduce unwanted pregnancy and sexually transmitted diseases. This work is presented as a series of journal entries. Through the use of prose and creative writing my participants and I begin to complicate our own understandings of sexuality and empowerment in context. I conclude that the insistence to complicate and situate such messy understandings in specific contexts is important for adult educators to move discussions around empowerment and sexuality forward.
Keywords: Sexuality; Empowerment; Community Development Workers; Pakistan